High-resolution hyaluronidase inhibition profiling combined with HPLC–HRMS–SPE–NMR for identification of anti-necrosis constituents in Chinese plants used to treat snakebite. (November 2015) - Liu, Yueqiu; Staerk, Dan; Nielsen, Mia N.; Nyberg, Nils; Jäger, Anna K.
Graphical abstract: Four hyaluronidase inhibitors, i.e., lansiumamide B (6 ), myricetin 3- O -β-d -glucopyranoside (7 ), vitexin (8 ) and 4′, 7-dihydroxy-5-methoxyflavone-8- C -β-d -glucopyranoside (9 ) were identified via high-resolution hyaluronidase inhibition profiling combined with HPLC–HRMS–SPE–NMR. Highlights: 22 out of 88 plant species inhibited necrosis enzymes from four snake venoms. Tannins were the main bioactive components responsible for the antinecrosis activity. HR hyaluronidase inhibition profiles aided pinpointing 4 active non-tannin compounds. Structural elucidation were based on HPLC–HRMS–SPE–NMR platform. Compound with previous unknown absolute structure identified from Clausena excavata . Abstract: Inhibition of the necrotizing hyaluronidase, phospholipase A2 and protease enzymes in four snake venoms by crude water and ethanol extracts of 88 plant species used against snakebites in traditional Chinese medicine was measured. High-resolution hyaluronidase inhibition profiles were constructed for the 22 plants showing highest hyaluronidase inhibition, and the results were used to guide subsequent structural analysis towards specific hyaluronidase inhibitors. Structural analysis was performed by high-performance liquid chromatography, high-resolution mass spectrometry, solid-phase extraction and nuclear magnetic resonance spectroscopy, i.e., HPLC–HRMS–SPE–NMR. This allowed identification of four non-tannin inhibitors, i.e., lansiumamide B (6 ) from Clausena excavata Burm.f., myricetin 3- O -β-d -glucopyranoside (7 ) from Androsace umbellata (Lour.) Merr., and vitexin (8 ) and 4′, 7-dihydroxy-5-methoxyflavone-8- C -β-d -glucopyranoside (9 ) from Oxalis corniculata L. Absolute configuration of 2, 3-dihydroxy- N -methyl-3-phenyl- N -[( Z )-styryl]propanamide (1 ) was determined using the Mosher method, which revealed two enantiomers, i.e., ( 2S, 3R )-2, 3-dihydroxy- N -methyl-3-phenyl- N -[( Z )-styryl]propanamide and ( 2R, 3S )-2, 3-dihydroxy- N -methyl-3-phenyl- N -[( Z )-styryl]propanamide with a ratio of 7:3.